Long term outcome of primary care depression. - Yiend, J; Paykel, E; Merritt, R; Lester, K; Doll, H; Burns, T (2009)
We conducted a follow up over 23 years of depressed patients originally presenting to general practice in 1981 and studied in detail at that time. Aims were to assess the long term course and outcome of depression in primary care. Patterns of recovery and recurrence of major depressive episodes, together with other aspects of course, treatment and current state, were assessed at interview. 78% (129) of the original sample were traced to current general practice and outcome data obtained on 54. One third had a prior history of depression. Interview data were obtained on 37 patients. Time to recovery from baseline averaged 10.3 months. The recurrence rate was 64% (23). Most participants suffered at least 2 further episodes that were frequently chronic lasting 2 years on average. Time before first recurrence appeared considerably longer than in comparable psychiatric inpatient samples. No participants were continuously ill. Although loss to follow up limits our conclusions, the course of primary care depression appears worse than suggested by previous, shorter follow ups. Our data suggest that long term risk of a recurrence may be high, but with recurrence delayed.